Defense against Foreign Interference: The Two-Tier Logic of UK Foreign Policy Shaping - K. A. Godovanyuk (Сравнительная политика, 2025)
The article explores the specific features of the UK strategic approach to policy towards Russia and China through the British establishment’s perception of threats to national security. Based on the Intermestic Realism theoretical model, the author analyses how the broad domestic political discourse influences strategic tasks being formulated in foreign policy and vise versa. The demand for the protection of the democratic process as widely seen now to be threatened by authoritarian regimes, as well as the emphasis on the counteraction against some state actors, have brought about the emergence of new narratives in the UK. These trends affect decision-makers in the field of foreign policy, and retain the potential to influence strategic culture regardless of which party the Cabinet belongs to. In terms of the UK-Russia and UK-China relations, two trends are emerging, related to the discourse on malicious interference and attempts at foreign influence not only on electoral and democratic processes, but also on public opinion, and, consequently, on the mainstream domestic political discourse. New law enforcement practices formulated in response to these challenges, on the one hand, provide some leeway in UK policy planning, and on the other hand, confine the policy only to a threat-centered discourse, creating long-term hard line towards Moscow and an increasingly less flexible approach towards Beijing.